10.61533 ANALISIS PERSEP UMKM & KUALITAS SUMBER DAYA MANUSIA (SDM) TERHADAP PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK-EMKM MENUJU EKONOMI BERKELANJUTAN DI KOTA PANGKALPINANG - Putri Tryanita; Medinal; Rizal R. Manullang (STIE IBEK Pangkalpinang, 2026)
This study aims to analyze the influence of Micro, Small, and Medium Enterprises (MSMEs) perceptions and the quality of Human Resources (HR) on the preparation of financial reports based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) in Pangkalpinang City. MSMEs are fundamental pillars of the national economy, but are often hampered by low accounting literacy and the quality of financial reporting. This study uses a quantitative approach with multiple linear regression methods. The research sample consisted of 86 MSMEs in Pangkalpinang City selected through purposive sampling techniques. Data collection was carried out through questionnaires and documentation. The results of the study indicate that (1) MSME perceptions have a positive and significant effect on the preparation of financial reports according to SAK-EMKM (tcount 7.164 > ttable 1.663); (2) HR quality also has a positive and significant effect on the preparation of financial reports (tcount 3.872 > ttable 1.663); and (3) Simultaneously, MSME perceptions and human resource quality significantly influence financial report preparation (Fcount 79.115 > Ftable 3.11). The coefficient of determination (R²) of 0.656 indicates that 65.6% of the variation in financial report preparation can be explained by these two variables. The implication of this study is the importance of improving accounting literacy and developing human resource capacity to promote transparency, accountability, and the contribution of MSMEs to a sustainable economy.